Characteristics and Efficacy of Warfarin Sodium Tablet Subdivided by 3D Printing Technology: A Retrospective Cohort Study of Patients After Prosthetic Valve Replacement - Lv J; Fu K; Xiong L; Chen B; Zhan L; Liu J; Lin Z; Yang F; Chen J (Drug Design, Development and Therapy)
Jieqiong Lv,1 Kaixia Fu,2 Lingjuan Xiong,3 Bishan Chen,4 Luchuan Zhan,3 Jiang Liu,3 Zhanyi Lin,5 Fan Yang,2,4 Jisheng Chen4 1Department of Pharmacy, The Second Affiliated Hospital of Shantou University Medical College, Shantou, Guangdong, People’s Republic of China; 2Guangdong Provincial Key Laboratory of Advanced Drug Delivery Systems and Guangdong Provincial Engineering Center of Topical Precise Drug Delivery System, Teaching Laboratory Center, Guangdong Pharmaceutical University, Guangzhou, Guangdong, People’s Republic of China; 3Department of Pharmacy, Guangdong Provincial People’s Hospital (Guangdong Academy of Medical Sciences), Southern Medical University, Guangzhou, Guangdong, People’s Republic of China; 4Key Specialty of Clinical Pharmacy, The First Affiliated Hospital of Guangdong Pharmaceutical University, Guangzhou, Guangdong, People’s Republic of China; 5Guangdong Geriatric Institute, Guangdong Provincial People’s Hospital (Guangdong Academy of Medical Sciences), Southern Medical University, Guangzhou, Guangdong, People’s Republic of ChinaCorrespondence: Fan Yang, Email gzyangfan@hotmail.com Jisheng Chen, Email cjslym@163.comBackground: Due to the individual-level clinical variation in dosing requirements in commercially available drugs, attaining the objective of clinical individualization and precise drug administration continues to pose a global challenge. Currently, the optimal approach for preparing personalized and precise medications within the clinical setting is unknown.Aim: This study aimed to explore the effectiveness, safety and satisfaction of three-dimensional (3D) printing technology as a novel subdivision method in providing precise warfarin sodium (WFS) subdivided tablets for patients after prosthetic valve replacement (PVR).Methods: The optimal formulation, preparation process, parameters, and the relationship between dose and the printing volume were investigated, and the quality of the six specifications of WFS 3D-printed subdivided and pharmacist-split tablets was studied. A retrospective cohort study evaluated the effectiveness, safety, and satisfaction of patients taking WFS 3D-printed subdivided or pharmacist-split tablets.Results: The hardness, weight variation, drug content, and content uniformity of the six specifications of WFS pharmacist-split tablets did not comply with the European Pharmacopoeia, United States Pharmacopoeia, and Chinese Pharmacopoeia. In contrast, all doses of 3D-printed subdivided tablets met the requirements. The 3D-printed subdivided group showed a significantly higher target international normalized ratio (INR) compliance rate (P< 0.05) and lower over-anticoagulation rate (P< 0.05) than the pharmacist-split group. Also, 66.67% of patients preferred taking 3D-printed subdivided tablets.Conclusion: 3D printing technology is superior to the traditional subdivision method, as it can improve the effectiveness and safety of patients receiving WFS anticoagulation after PVR. Keywords: 3D printing technology, warfarin sodium, subdivided tablets, clinical efficacy, a retrospective study